2022
DOI: 10.1007/s10554-021-02519-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of impaired longitudinal left ventricular systolic function assessed by tissue Doppler imaging prior to transcatheter aortic valve implantation for severe aortic stenosis

Abstract: Change in longitudinal left ventricular (LV) systolic function serves as an early marker of the deleterious effect of aortic stenosis (AS) and other cardiac comorbidities on cardiac function. We explored the prognostic value of tissue Doppler imaging (TDI)-derived longitudinal LV systolic function, defined by the peak systolic average of lateral and septal mitral annular velocities (average S’) among symptomatic patients with severe AS undergoing transcatheter aortic valve implantation (TAVI). 297 consecutive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The benefit of adopting this parameter is the high temporal resolution, ease and reproducibility when evaluating myocardial motion throughout the cardiac cycle which can be broken down into systolic and diastolic components 42 . A recent study evaluating the assessment of mitral annular peak systolic (S’) velocities in severe AS patients identified that S’ is independently correlated with all‐cause mortality (per 1 cm/sec reduction: HR 1.29, 95% CI 1.03–1.60, p = .025), with an average S’ < 6.5 cm/sec illustrating progressive LV remodelling and higher mortality rates (17.6% vs. 7.5%, p = .007) when compared to those with averaged S' values above 6.5 cm/sec 41 . Another investigation evaluating the combined role of TDI and N‐terminal Pro‐Brain Natriuretic Peptide highlighted the increased incremental prognostic data in asymptomatic moderate to severe AS patients when compared to each parameter independently 43 .…”
Section: Quantification Of Myocardial Motion: Tissue Doppler and Defo...mentioning
confidence: 98%
See 3 more Smart Citations
“…The benefit of adopting this parameter is the high temporal resolution, ease and reproducibility when evaluating myocardial motion throughout the cardiac cycle which can be broken down into systolic and diastolic components 42 . A recent study evaluating the assessment of mitral annular peak systolic (S’) velocities in severe AS patients identified that S’ is independently correlated with all‐cause mortality (per 1 cm/sec reduction: HR 1.29, 95% CI 1.03–1.60, p = .025), with an average S’ < 6.5 cm/sec illustrating progressive LV remodelling and higher mortality rates (17.6% vs. 7.5%, p = .007) when compared to those with averaged S' values above 6.5 cm/sec 41 . Another investigation evaluating the combined role of TDI and N‐terminal Pro‐Brain Natriuretic Peptide highlighted the increased incremental prognostic data in asymptomatic moderate to severe AS patients when compared to each parameter independently 43 .…”
Section: Quantification Of Myocardial Motion: Tissue Doppler and Defo...mentioning
confidence: 98%
“…Longitudinal function derived by amendments in filter settings used to visualize high‐intensity, low velocity signals allow the capability to interrogate myocardial motion over time at specific regions using pulse wave Doppler 37 . TDI is a well‐established, standardized approach to evaluate cardiac longitudinal function during TTE and validated in numerous cardiac comorbidities including diastolic dysfunction, 38 atrial fibrillation, 39 diabetes, 40 and AS 41 . The benefit of adopting this parameter is the high temporal resolution, ease and reproducibility when evaluating myocardial motion throughout the cardiac cycle which can be broken down into systolic and diastolic components 42 .…”
Section: Quantification Of Myocardial Motion: Tissue Doppler and Defo...mentioning
confidence: 99%
See 2 more Smart Citations